2014
DOI: 10.1096/fj.14-257352
|View full text |Cite
|
Sign up to set email alerts
|

MUC16: molecular analysis and its functional implications in benign and malignant conditions

Abstract: MUC16 is a high-molecular-weight glycoprotein that is expressed by the various epithelial cell surfaces of the human body to protect the cell layer from a myriad of insults. It is the largest mucin known to date, with an ∼22,152 aa sequence. Structurally, MUC16 is characterized into 3 distinct domains: the amino terminal, the tandem repeat, and the carboxyl terminal domain, with each domain having unique attributes. The extracellular portion of MUC16 is shed into the bloodstream and serves as a biomarker for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 133 publications
3
98
0
Order By: Relevance
“…The ectodomain has a massive (12,000 amino acid) O-glycosylated domain, a tandem repeat domain consisting of more than 60 repeats of 156 amino acids, and S perm-E nterokinase-A grin (SEA) domains (O'Brien et al 2001 ;Yin and Lloyd 2001 ;Gipson et al 2014 ). Indirect evidence for the occurrence of MUC16 splice variants has been suggested [discussed in Haridas et al ( 2014 )]; however, mRNA splice variants have not been rigorously identifi ed. Fragments of MUC16 released from the cell surface are the CA 125 antigens commonly used as a serum marker for certain cancers, notably ovarian and endometrial (Patsner and Yim 2013 ;Baser et al 2014 ;Felder et al 2014 ), as well as endometriosis (Spaczynski and Duleba 2003 ).…”
Section: Structurementioning
confidence: 99%
“…The ectodomain has a massive (12,000 amino acid) O-glycosylated domain, a tandem repeat domain consisting of more than 60 repeats of 156 amino acids, and S perm-E nterokinase-A grin (SEA) domains (O'Brien et al 2001 ;Yin and Lloyd 2001 ;Gipson et al 2014 ). Indirect evidence for the occurrence of MUC16 splice variants has been suggested [discussed in Haridas et al ( 2014 )]; however, mRNA splice variants have not been rigorously identifi ed. Fragments of MUC16 released from the cell surface are the CA 125 antigens commonly used as a serum marker for certain cancers, notably ovarian and endometrial (Patsner and Yim 2013 ;Baser et al 2014 ;Felder et al 2014 ), as well as endometriosis (Spaczynski and Duleba 2003 ).…”
Section: Structurementioning
confidence: 99%
“…MUC16 is believed to play important roles not only in normal contexts such as reproduction and proliferation, but also in pathologic states including cancer and mucosal infections. It exerts its function in cancer by many mechanisms such as migration, invasion, cell cycle control and metabolism reprogramming (16,17). Since its discovery, CA125 is usually used as a tumor marker, and many efforts have been given to its contribution to tumor malignancies, yet little is known about its regulation.…”
Section: Introductionmentioning
confidence: 99%
“…It has a short transmembrane domain and cytoplasmic tail of 32 amino acids. (For review of MUC16 structure see Haridas et al (Haridas et al, 2014), and Govindarajan and Gipson (Govindarajan and Gipson, 2010)). An antibody, termed H185, specific to a glycan on MUC16 (Argueso et al, 2003) was found by immunoelectron microscopy to bind microplicae on the surface of human corneal and conjunctival epithelium, but the antibody was also found to bind to goblet cell mucin packets in human conjunctival epithelium obtained by impression cytology (Danjo et al, 1998).…”
mentioning
confidence: 99%